Amylolytic activity of selected species of ruminal bacteria. - Cotta, M A (1988)
A variety of species of ruminal bacteria were screened for the ability to grow in starch-containing medium and produce amylase. Of those tested, the highest levels of amylase were produced by Streptococcus bovis JB1 and Ruminobacter amylophilus H18. Other strains that grew well on starch and produced amylase included Butyrivibrio fibrisolvens A38 and 49 and Bacteroides ruminicola 23 and B14. Varying the carbohydrate source provided for growth resulted in changes in the growth rate and level of amylase produced by these strains. All strains grew rapidly in starch-containing medium, and the rates of growth were generally more rapid than those observed for maltose-grown cultures. For S. bovis JB1, B. ruminicola 23 and B14, and B. fibrisolvens 49 and A38, amylase was produced when growth was on maltose or starch, but this activity was greatly reduced in glucose-grown cultures. The distribution of amylolytic activity between cellular and extracellular fractions was sometimes affected by the carbohydrate provided for growth. If S. bovis JB1 and B. fibrisolvens 49 were grown on starch, amylase was largely associated with cell pellets; however, if grown on maltose these strains produced activities that were almost entirely present in the extracellular fluid fractions. Although not as dramatic, a similar shift in the location of amylase activities was noted for the two B. ruminicola strains when grown on the same substrates. Growth on maltose or starch had little influence on either the predominantly cell-associated activity of B. fibrisolvens A38 or the activity of R. amylophilus H18, which was equally divided between cell pellet and extracellular fluid fractions.(ABSTRACT TRUNCATED AT 250 WORDS)